Genetic polymorphism in the NRF2 gene as a prognosis marker for cancer chemotherapy - Ishikawa, Toshihisa (Frontiers in Genetics, 2014)
The transcription factor NF-E2-related factor 2 (NRF2) is known to control cellular adaptation/protection to reactive oxygen species and electrophiles by inducing antioxidation and detoxification genes as well as to mediate cancer cell proliferation and drug resistance. The SNP -617C>A in the anti-oxidant response element (ARE)-like loci of the human NRF2 gene play a pivotal role in the positive feedback loop of transcriptional activation of the NRF2 gene. Since the SNP (-617A) decreases the binding affinity to the transcription factors of NRF2/small MAF (MafK), it is anticipated that the homozygous -617A/A allele attenuates the positive feedback loop of transcriptional activation of the NRF2 gene and thereby reduces the NRF2 protein level. As the consequence, cancer cells may become more sensitive to therapy and less aggressive than cancer cells harboring the -617C (WT) allele. Indeed, Japanese lung cancer patients carrying SNP homozygous alleles (c.-617A/A) exhibited remarkable survival over 1,700 days after surgical operation (log-rank p = 0.021). The genetic polymorphism in the human NRF2 gene is considered as one of prognosis markers for cancer therapy.